PERBEDAAN PENGARUH RASIO KERJA ISTIRAHAT LATIHAN INTERVAL ANAEROB DAN KAPASITAS AEROB TERHADAP KECEPATAN LARI 100 METER PUTRA - RATNA KUMALA SETYANINGRUM (Universitas Tunas Pembangunan, 2012)
The study is aimed at find out: (1) The difference of effect on anaerobic interval practice with break rasio of 1:10, 1:15 and 1:20 to the speed of 100 meter sprint, (2) The difference of effect on the amount of aerobic capacity during practice to the speed of 100 meter sprint, (3) The interaction between the rasio difference of practice-break in anaerobic interval practice and aerobic capacity to the speed of 100 meter sprint. The study uses an experimental method which contains three variabels, i.e. manipulative free variabel (practice method), attributive variabel (aerobic capacity), and bound variabel (the speed of 100 meter sprint). The design of the study is the factorial 3x3. The sample used in this study is all 100 meter sprint male athletes in SMP Kabupaten Temanggung year 2011, as many as 40. The sample collection was conducted by purposive random sampling. The data of aerobic capacity was obtained by a Multistage Fitness Test, while the 100 meter sprint speed was measured by a 100 meter sprint test. The data was analyzed using ANAVA technique. Prior to using ANAVA test, a sample normality test (Lilliefors test with Î± = 0.05) and a variance homogeneity test (Bartlet test with Î± = 0.05) was conducted. The results of the study show that: (1) There are many differences about anaerob interval exercise by rasio 1:10, 1:15 and 1:20 to increase the result the fast running 100 m. F (count) = 7.88 > F (table) = 4.15. The effect of anaerob interval exercise 1:15 more better than 1:20 and 1:10, the value is 1.20, for low aerobic capacity more better use rasio 1:20. (2) There are many differences effect between the higher aerob capacity, medium aerobic capacity for the result the fast running 100 m. F (count) = 6.56 > F (table) = 4.15. The increasing product the fast running 100 m, the higher aerob capcity are more better than the sample who have medium or lower aerob capacity. (3) There are many interaction between rasio difference of practice- Â break in anaerobic interval practice and aerobic capacity to the speed of 100 meter sprint. F (count) = 3.30 > F (table) = 4.15.